The Effectiveness of Kelor Leaves Powder on The Production of Breast Milk and Immunoglobulin A (Ig.A) - Kuswanto Kuswanto; Heru Purnomo; Dina Dewi Anggraini (JURNAL KEBIDANAN, 2020)
Nutrition problems in infants are still a public health problem that is often found in Indonesia. Malnutrition due to lack of breast milk has not been resolved, and the prevalence of nutritional problems is starting to increase. Composition of ASI contains essential nutrients that are sufficient for the baby even though the mother is in a state of malnutrition and is able to overcome infection through phagocyte and immunoglobulin cell components. Moringa leaves are proven to increase the nutrition of breast milk, containing Amino Acid and high enough protein that can improve the quality of breast milk. The purpose of this study to determine the effectiveness of Moringa leaf powder in increasing the production of exclusive breastfeeding and increasing immunoglobulin A (Ig.A) in infants. This research uses quantitative research with quasi-experimental method with a pre-post test design research design. The sample in this study was breastfeeding mothers with lack of milk production. The number of respondents in this study were 60 respondents breastfeeding mothers who were divided into control groups and treatment groups. Analysis of research results using the Wilcoxon test. Tha result showed that value of Zcount = 6.600 Ztable = 1.645 and p-value = 0.003 (0.05). Based on the results of this analysis it can be concluded that there is an effect of the effectiveness of Moringa leaf powder on increasing the production of exclusive breastfeeding and immunoglobulin A (Ig.A) in infants.